1999
DOI: 10.1099/0022-1317-80-2-447
|View full text |Cite
|
Sign up to set email alerts
|

The major immunogenic epitopes of Epstein-Barr virus (EBV) nuclear antigen 1 are encoded by sequence domains which vary among nasopharyngeal carcinoma biopsies and EBV-associated cell lines.

Abstract: Epstein-Barr virus (EBV) nuclear antigen 1 (EBNA-1) is a protein expressed consistently in EBV-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 32 publications
2
22
0
Order By: Relevance
“…Because most of the polymorphic regions were found to match putative MHC class I binding epitopes, it was suggested that these variations could contribute to the immune escape of EBV in EBV-associated malignant diseases. This hypothesis was supported partly by our finding that the regions of sequence variation of EBNA-1 were dominant immunogenic epitopes in the mouse [Chen et al, 1999].…”
Section: Introductionmentioning
confidence: 56%
“…Because most of the polymorphic regions were found to match putative MHC class I binding epitopes, it was suggested that these variations could contribute to the immune escape of EBV in EBV-associated malignant diseases. This hypothesis was supported partly by our finding that the regions of sequence variation of EBNA-1 were dominant immunogenic epitopes in the mouse [Chen et al, 1999].…”
Section: Introductionmentioning
confidence: 56%
“…An EBNA-1 monoclonal antibody tag system was therefore used to enhance the specificity of the immunoprecipitation reaction. 5C11 recognizes an epitope between amino acids 408 and 446 of EBNA-1, a region which contains no serine or threonine residues, and was shown to react with this sequence in both immunoprecipitation and Western immunoblot assays (8). Therefore, EBNA-1(408-446) and BGLF4 were expressed as a fusion protein using a derivative of pGH254 which contains a T7 RNA promoter and a black beetle virus leader sequence to enhance translation (18).…”
Section: Resultsmentioning
confidence: 99%
“…This is a derivative of pBD7 (18) and contains a T7 promoter sequence and a black beetle virus leader sequence to enhance protein expression levels. The BamHI DNA fragment containing BGLF4 was subcloned into the BglII site of pGH254, and then a PCR product, encoding amino acids 408 to 446 of EBNA-1, was cloned upstream of BGLF4 as a tag for detection and immunoprecipitation with monoclonal antibody 5C11 (8). This construct was designated pSJC12(E1/BGLF4).…”
Section: Plasmid Constructionmentioning
confidence: 99%
See 1 more Smart Citation
“…NP_001562), IRF3Ј lacks part of the IAD (aa 327 to 375) and the transactivation domain (aa 327 to 394) of the IRF3 protein. To confirm the interaction between BGLF4 and IRF3Ј, 293T cells were cotransfected with E1/BGLF4(1-293) and HA-IRF3Ј(282-452) expression constructs and subjected to coimmunoprecipitation with E1 tag-specific MAb 5C11 (13). HA-IRF3Ј(282-452) was coimmunoprecipitated from cell extracts specifically with E1/BGLF4(1-293) (Fig.…”
Section: Interaction Of Bglf4 Kinase With a Cellular Irf3 Variantmentioning
confidence: 98%